Nanotechnologies in regenerative medicine - Kubinová, Sárka; Syková, Eva (Minimally invasive therapy & allied technologies, 2010)
Nanotechnology offers promising perspectives in biomedical research as well as in clinical practice. To cover some of the latest nanotechnology trends in regenerative medicine, this review will focus on the use of nanomaterials for tissue engineering and cell therapy. Nanofibrous materials that mimic the native extracellular matrix and promote the adhesion of various cells are being developed as tissue-engineered scaffolds for the skin, bone, vasculature, heart, cornea, nervous system, and other tissues. A range of novel materials has been developed to enhance the bioactive or therapeutic properties of these nanofibrous scaffolds via surface modifications, including the immobilization of functional cell-adhesive ligands and bioactive molecules such as drugs, enzymes and cytokines. As a new approach, nanofibers prepared by using industrial scale needleless technology have been recently introduced, and their use as scaffolds to treat spinal cord injury or as cell carriers for the regeneration of the injured cornea is the subject of much current study. Cell therapy is a modern approach of regenerative medicine for the treatment of various diseases or injuries. To follow the migration and fate of transplanted cells, superparamagnetic iron oxide nanoparticles have been developed for cell labeling and non-invasive MRI monitoring of cells in the living organism, with successful applications in, e.g, the central nervous system, heart, liver and kidney and also in pancreatic islet and stem cell transplantation.
Keywords: Tissue Engineering; Transplants; transplantáty; magnetická rezonanční tomografie; nanomedicína; Biomedical Research; Magnetite Nanoparticles; extracelulární matrix; tkáňové inženýrství; Nanomedicine; magnetické nanočástice; buněčná a tkáňová terapie; biomedicínský výzkum; lidé; nanovlákna; Wound Healing; Cell- and Tissue-Based Therapy; Humans; Extracellular Matrix; Tissue Scaffolds; Nanofibers; Regenerative Medicine; regenerativní lékařství; Nanotubes, Carbon; tkáňové podpůrné struktury; Magnetic Resonance Imaging; nanotrubičky uhlíkové; hojení ran